(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Abstract. This paper deals with applications in topological optimization problems via numerical technique SESO - Smooth ESO. In particular, non-trivial problems of specificÂ projects of two-dimensional elastic structures are simulated. These problems have different characteristics and are also treated with different approaches in this work. A restriction called Nibbling allows the SESO technique performing changes in shape / perimeter of the structure topology. Such constraint technique has been implemented and coupled into the optimization process in order to control inappropriate creation of cavities in extended fixed domain. The influence of the number of cavities, created in that domain due to the variation of the insertion rate of cavities called TIC, is discussed. In addition, the technique of topology optimization SESO has been extended to consider regions as non-design domain. Classic examples of topological optimization are presented and proving the efficiency of SESO technique and of new implementations described in this paper. Keywords: Topology optimization, Smooth Evolutionary Structural Optimization, Nibbling